PENGARUH KONSENTRASI Li YANG DI-DOPING KE DALAM KATALIS CaO TERHADAP REAKSI TRANSESTERIFIKASI MINYAK SAWIT - Muhammad Tarmidzi; Andre Y. Putra; Renita Manurung; Tjahjono Herawan (Jurnal Teknik Kimia USU, 2013)
The development of biodiesel which is derived from Crude Palm Oil (CPO) shows a risingtrend forpetroleum-based energy reserves are running low.Oil palm is the largestplantation commodity in Indonesia, so, it has high potential as raw material of biodiesel.Transesterification is a reaction of producingbiodiesel (methyl ester). Nevertheless, CPO is easy to be degraded byhydrolysis, so, it couldincrease the amount of Free Fatty Acid (FFA) content which hampers transesterification process. As a consequence, there is formation of soaps as side product. Tomaximize the production of biodiesel which is derived frompalm oil that contains of large amount of FFA (low grade CPO) one of the waysis by applying catalyst through doped-process. This research is held togive information about the effect of Li+ion concentration (inLiNO3 form) which is doped to calcium oxide (CaO) to palm oil transesterification with the large amount ofFFA to produce methyl ester, attemperature of 120oC,the ratio of methanol:CPO = 12:1 (mol/mol), catalyst amount 2,5% (w/w) CPO, for 3,5 hours and usespressured reactor. The variable of research is Liconcentration that isdoped to CaO with concentration: 0%, 1% and 4% (w/w) CaO. The parameter test is methyl ester content that is derived from the result of transesterification with GasChromatography (GC) analysis. The research shows that Li+ion that is doped to CaO catalyst could increase the reaction of methyl ester production which is derived from low grade CPO with FFA>3,5 %, in which the finest of Liconcentration that is doped to CaO is 1%, with result of 90,88% methyl ester.